Hồ Chí Minh Thought on International Relations of the Vietnamese Revolution in the 1920s - Thành, Phạm Quốc (VNU Journal of Science: Social Sciences and Humanities; Vol 29 No 4, 2013)
Abtracts: From the poitns of view of Hồ Chí Minh, the revolutionary goal was to liberate the weak nation, then, move on to revolutionize the world, all humanity will be released from the imperialist and capitalist. He pointed out, there are two kinds of the revolution such as the national revolution and the world revolution; the revolutionary career is great and difficult to implement, it cannot done by one person or a family but by all peasants, the workers in the world of any country, any race race joined together as a close family, to knock down all the capitalist in the world, making the country and people be always happy to do for lower natural universality. And the imperialists in all the countries allied to oppress us so we have to join forces to fight them, which means that all oppressed people and all workers in the world need to unite for a revolution. In a book under the title The Revolutionary Path , Hồ Chí Minh pointed out that the Annam Revolution was also a part of the world Revolution; whoever made revolution in the world are all our comrades; Annamese empire struggled againts the French imperialitst; more revolutionary people are likely to sacrifice, to face with misery; need the help from brothers in the world. At the same time, he said "Our revolution must contact with all revolutionary parties in the world against capitalism and imperialism".       Keywords: Flood, inundation, flood risk hazard, Hanoi City.